Structure of Contextual Synonymic Rows in Russian and English Newspapers: Ecolinguistic and Contrastive Aspects - A. V. Moiseenko; L. A. Gunko (Научный диалог, 2017)
The article deals with the aspects of contextual synonyms functioning in Russian and English newspaper texts united by the theme of refugee migration in Europe. The relevance of the work is determined by its interdisciplinarity and combination of contrastive and ecolinguistic approaches. Contrastive approach consists in identification of common and distinctive features of the synonymic rows in English and Russian newspapers. Ecolinguistic approach involves determining the intensity of use of substandard tokens in the contextual synonymic rows. The research material are 18 contextual synonymic rows, formed by 4 newspapers - “Kommersant,” “Komsomolskaya Pravda,” “The Guardian Weekly,” “The Daily Mail.” The paper discusses the concept of contextual synonym and contextual synonymic row. There are 3 models of synonymic row including: (1) only literary units; (2) literary and colloquial lexemes; (3) literary, colloquial and substandard units. It was revealed that news texts in Russian and English high-quality publications characterized by the presence of expert assessments and targeted at the educated reader, differ by homogeneous material flow and primarily using standard tokens. Tabloid edition aimed at a wide readership often use colloquial synonyms. It is determined that Russian-language rows have a higher coefficient of colloquialisms (17.2 %) than the English (4.8 %).